Razao Sr:Ba:Rb e tipologia de zircao em granitoides dos Estado de Sao Paulo, Parana e Minas Gerais - Wernick, E.; Rigo, L.; Galembeck, T. M B; Artur, A. C.; Weber- Diefenbach, K. (My University, 1990)
Chemical (Sr:Ba:Rb) and zircon typology data from the Nazare Paulista, Mairipora/Cantareira, Cunhaporanga, Tres Corregos, Morungaba, Socorro, Itu, Graciosa and Serra Carambei granitoid complexes from the states of Minas Gerais, Sao Paulo and Parana (SE/S Brazil) are presented and discussed. By the zircon typology method these complexes are refered, respectively, to the 2nd crustal, 3rd crustal/low temperature C-A, low temperature C-A, medium temperature C-A, medium/light temperature C-A, K-SA/Alkaline and alkaline series which are considered as generated under increasing temperature associated with a progressive major participation of mantle material. All these series display different positions and behaviour in the Sr:Ba:Rb diagram which reinforces the use of the zircon typology method in the study of granitoids. -from English summary
The Sr:Ba:Rb ratio and zircon typology in granitoid complexes of Sao Paulo, Parana and Minas Gerais, Brazil
Keywords: geochemistry; granite; petrogenesis; zircon; Brazil, Minas Gerais; Brazil, Parana; Brazil, Sao Paulo